Distribution of Soil Fertility of Smallholding Arabica Coffee Farms at Ijen-Raung Highland Areas Based on Altitude and Shade Trees - Niken Puspita sari; Teguh Iman Santoso; Surip Mawardi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Soil fertility is one of the most important factors influencing plant growth and productivity and it depends on the availability and quantity of nutrients in the soil. To study soil fertility status of an area, a study on soil chemistry and physics has to be conducted. The aim of this study was to investigate soil fertility status of smallholding Arabica coffee farms based on altitude and shades trees utilization. This research was carried out in April-August 2012 at IjenRaung highland areas by field survey. The results showed that the soil contained high content of organic carbon, nitrogen total, and C/N ratio; low available phosphorus; moderate to high cation exchange capacity, and low base cation of calcium, magnesium, and potassium; as well as slightly low pH. Higher altitude tended to have higher C organic and N total content, C/N ratio as well as pH. In contrast, in lower altitude tended to have lower available P, base saturation, as well as Ca, Mg, and K content. The dominant shade trees for coffee farming at the Ijen-Raung highland areas were suren (Toona sureni) , dadap (Erythrina sp.), kayumanis (Cinnamomum zeylanicum), pinus (Pinus mercusii), and kayu putih (Eucalyptus globulus). Different shade tree species resulted in different of soil fertility. Shade trees tended to influence cation exchange capacity from moderate to high, pH slightly acid, high base saturation, and low P available. Suren tree influenced better base cation than that of other trees but dadap tree was better in increasing soil fertility. Key word: Soil fertility, arabica coffee, andisol, shade trees, smallholding